Bibliometric analysis of confidence interval methods for mean estimation in statistical research / Siti Fairus Mokhtar, Zahayu Md Yusof and Hasimah Sapiri - Mokhtar, Siti Fairus; Md Yusof, Zahayu; Sapiri, Hasimah (Universiti Teknologi MARA, Kedah, 2024)
This study examines the development of confidence intervals for mean through a bibliometric approach through computational mapping analysis using VOSviewer. This paper aims to examine confidence interval and mean using bibliometric analysis. This paper also analyzes sources of publication, authorship, citations, distribution publications, and other bibliometric indicators. A bibliometric method was adopted. Literature published in academic journals indexed in the Scopus database was retrieved. The study period was set from 1950 to 2023. The study recalled 382 documents from 1950 to 2023 using keywords related to the research topic. It was analyzed using Microsoft Excel 2019, VOSviewer software, and Harzing's Publish or Perish software. The documents were retrieved to rank the most productive countries, institutions, authors, keywords, influential articles, and the topic model. The findings show that the top publication journals are Communications in Statistics Theory and Methods and Communications in Statistics Simulation and Computation. The top keywords in this research include confidence interva and coverage probability. Countries such as the United States, Thailand, and Taiwan dominate the publication of this area of study. This investigation provides a recent review of this fast-growing field to highlight status and trends using network visualization and bibliometric indicators. The findings are hoped to aid researchers in identifying and exploring potential emerging areas in the related field.